Maximos von Tyros und Apologie des Sokrates - Belikov, Grigory (Hyperboreus, 2025)
The third speech of Maximus of Tyre “Whether Socrates was right not to speak in his own defence” was little researched, although it is an original text connected with the tradition of Socratic writings. In this article this speech is considered in the light of the tradition of writing Socrates’ Apologies, as well as in the literary context of the I–II centuries AD. The third speech of Maximus can hardly serve as a historical source for the reconstruction of Socrates’ trial, since it is based on the common biographical tradition and does not contain any unique historical data. At the same time, it is wrong to consider this speech as a rhetorical exercise based on a paradoxical thesis, following some researchers (M. Szarmach, J. Puigalli). Maximus does not try to prove that Socrates did not defend himself in court. The main question to which the speech is devoted is why Socrates did not prepare an apology according to the rules of rhetoric. This formulation corresponds quite well to the main idea of Xenophon’s Apologia Socratis: he did not prepare a speech because he had preferred death to life (Xen. Ap. Socr. 1). However, there are no direct references to this text of Xenophon in the third speech. Maximus used material from Plato’s Apologia Socratis, and there are also references to the dialog Gorgias. The argumentation in this speech is built around the opposition between Socrates as a true philosopher and the Athenians who were not worthy to judge him.